Complexity and Diversity of the NKR-P1:Clr (Klrb1:Clec2) Recognition Systems - Kirkham, Christina L.; Carlyle, James R. (Frontiers in Immunology, 2014)
The NKR-P1 receptors were identified as prototypical natural killer (NK) cell surface antigens and later shown to be conserved from rodents to humans on NK cells and subsets of T cells. C-type lectin-like in nature, they were originally shown to be capable of activating NK cell function and to recognize ligands on tumour cells. However, certain family members have subsequently been shown to be capable of inhibiting NK cell activity, and to recognize proteins encoded by a family of genetically linked C-type lectin-related (Clr) ligands. Some of these ligands are expressed by normal, healthy cells, and modulated during transformation, infection, and cellular stress, while other ligands are upregulated during the immune response and during pathological circumstances. Here, we discuss historical and recent developments in NKR-P1 biology that demonstrate this NK receptor-ligand system to be far more complex and diverse than originally anticipated.